Study the influence of Annealing upon electrical properties of The prepared films ZnSe by Thermal evaporation in Vacuum (Baghdad Science Journal, 2004)
Thin films of ZnSe arc deposited on glass substrates by thermal evaporation in vacuum with different thickness (1000, 2700, 4000) A° temperature (293-373) °K are studies the electrical properties before and after annealing. The result show decrease D.0 conductivity and increasing the activation energy Eat.